2020
DOI: 10.3390/f11111192
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Diversity and Structure of Ancient Tree Populations of Cryptomeria japonica var. sinensis Based on RAD-seq Data

Abstract: Research highlights: Our study is the first to explore the genetic composition of ancient Cryptomeria trees across a distribution range in China. Background and objectives: Cryptomeria japonica var. sinensis is a native forest species of China; it is widely planted in the south of the country to create forests and for wood production. Unlike Cryptomeria in Japan, genetic Chinese Cryptomeria has seldom been studied, although there is ample evidence of its great ecological and economic value. Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 62 publications
3
21
1
Order By: Relevance
“…We found evidence of genetic differentiation among populations of L. praecox, L. umbellata, and L. obtusiloba as has often been reported for other plant species [37][38][39]. First, AMOVA results indicated that regional variation explained a large proportion of the total variation (Table 5).…”
Section: Discussionsupporting
confidence: 75%
“…We found evidence of genetic differentiation among populations of L. praecox, L. umbellata, and L. obtusiloba as has often been reported for other plant species [37][38][39]. First, AMOVA results indicated that regional variation explained a large proportion of the total variation (Table 5).…”
Section: Discussionsupporting
confidence: 75%
“…During that time, gene flow from C. mollicoma to C. monbeigiana may have been influenced by climate change, which created a condition of novel contact. We also found that the genetic divergence ( F ST ) between the two species was at a lower level (∼0.109) when compared with the recent studies on poplar tree ( Chhatre et al, 2018 ; Cai et al, 2020 ). This may be caused by the relative gene flow between them that eliminates divergence at non-selecting regions ( Han et al, 2017 ).…”
Section: Discussionsupporting
confidence: 43%
“…Microsatellites are often used for studies of genetic diversity and population structure, for example in plants ( Zhang et al, 2019 ; Islam et al, 2020 ; de Dato et al., 2020 ), although generating large amounts of single nucleotide polymorphism (SNP) data has become a standard option in many population genetics studies ( e.g. , Pina-Martins et al, 2019 ; Feng et al, 2020 ; Cai et al, 2020 ; Vanhove et al, 2021 ). Microsatellites are particularly useful for detecting weak contemporary differences and shallow structuring among populations, and thus for inferring information on gene flow among populations on a fine spatial scale, despite having a higher genotyping error rate and low density across genomes, compared to SNPs ( DeFaveri et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%